1997
DOI: 10.1099/00221287-143-12-3703
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing and Chromobacterium violaceum: exploitation of violacein production and inhibition for the detection of N-acylhomoserine lactones

Abstract: Quorum sensing relies upon the interaction of a diffusible signal molecule with a transcriptional activator protein to couple gene expression with cell population density. In Gram-negative bacteria, such signal molecules are usually N-acylhomoserine lactones (AHLs) which differ in the structure of their N-acyl side chains. Chromobacterium violaceurn, a Gram-negative bacterium commonly found in soil and water, produces the characteristic purple pigment violacein. Previously the authors described a violacein-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
1,424
3
29

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,573 publications
(1,470 citation statements)
references
References 39 publications
14
1,424
3
29
Order By: Relevance
“…Inhibition of QS regulated violacein production in C. violaceum is commonly used for anti-QS screening studies. The AHL synthesized by different strains of C. violaceum vary in their acyl chain length or substitution, and the two wild type strains used in this study though produce two different major AHL molecules [11] , the tested plant extracts were able to inhibit the violacein synthesis in both. Other reports have also found natural plant extracts, such as that of Myristica cinnamomea, showing anti-QS activity at 3 mg/mL against C. violaceum CV026 [14] .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Inhibition of QS regulated violacein production in C. violaceum is commonly used for anti-QS screening studies. The AHL synthesized by different strains of C. violaceum vary in their acyl chain length or substitution, and the two wild type strains used in this study though produce two different major AHL molecules [11] , the tested plant extracts were able to inhibit the violacein synthesis in both. Other reports have also found natural plant extracts, such as that of Myristica cinnamomea, showing anti-QS activity at 3 mg/mL against C. violaceum CV026 [14] .…”
Section: Discussionmentioning
confidence: 85%
“…Biosensor bioassay for anti-QS activity was carried out according to the methods described previously [11] . Briefly, plant extracts re-suspended in ethanol were loaded onto 6 mm sterile discs (Himedia, India) at different concentrations (100 µg-3.0 mg/disc).…”
Section: Biosensor Bioassay For Detecting Anti-qs Activity Of the Plamentioning
confidence: 99%
See 1 more Smart Citation
“…The AHL degradation activity of the different extracts was tested by incubating 500 μl of each extract with N -hexanoyl-L-homoserine lactone (C6-HSL) 10 μM for 24 h at 22°C 200 rpm and the remaining AHL was detected using the biosensor strain Chromobacterium violaceum CV026 [39,40]. After 24 h of degradation, 100 μl of the mixture were placed in wells made on an LB plate overlaid with a 1/100 dilution of an overnight culture of C. violaceum CV026 in soft LB (8% agar).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that C6-HSL also acts as an AHL and induces violacein production in the wild-type strain of Chromobacterium violaceum. 7) The physiological function of C14-HSL is unknown at present, but it might play an important role in the quorum sensing regulation of other bacterial behaviors. Strain 520P1 (1 ml) was incubated in the wells of a 24-well plate with 62 mM 3-oxo-C8-HSL standard, 48 mM C14-HSL standard, or 100 ml of the AHL sample extracted from the spot corresponding to 3-oxo-C8-HSL on a TLC plate (A).…”
mentioning
confidence: 99%